2019
DOI: 10.3390/ijerph16224369
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Racial and Ethnic Discrimination Are Associated with Food Insecurity and Poor Health

Abstract: This study examines the associations of mothers’ experiences of discrimination (EODs) with household food insecurity (HFI), physical health, and depressive symptoms, while taking into account the influence of mothers’ Adverse Childhood Experiences (ACEs) and public assistance participation. Mothers (N = 1372) of young children under age 4 who self-identified as Latinx, Non-Latinx Black/African American and Non-Latinx white answered questions for a cross-sectional survey in an emergency room in a large children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 51 publications
3
37
2
1
Order By: Relevance
“…The small number of prior investigations regarding this relationship have focused on households with children (13,14) . For example, research involving Latinx and Black/African American mothers of young children in Philadelphia found that experiences of discrimination from police, courts and in workplaces were associated with a greater likelihood of being food insecure (13) . Discrimination in workplaces, schools and courts as examined by existing studies might plausibly be linked to greater food insecurity by pathways involving higher rates of incarceration, lower wages, lower rates of promotion and poorer job security.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of prior investigations regarding this relationship have focused on households with children (13,14) . For example, research involving Latinx and Black/African American mothers of young children in Philadelphia found that experiences of discrimination from police, courts and in workplaces were associated with a greater likelihood of being food insecure (13) . Discrimination in workplaces, schools and courts as examined by existing studies might plausibly be linked to greater food insecurity by pathways involving higher rates of incarceration, lower wages, lower rates of promotion and poorer job security.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to underlying mechanisms on the pathway from food insecurity to ED pathology, there are undoubtedly a number of important mechanisms to explore. One such possibility might be to investigate the roles of stigma and discrimination, as food insecurity is associated with higher levels of weight stigma [ 45 ••] and experiences of racial/ethnic discrimination [ 80 ]. In addition to elucidating temporality and underlying mechanisms, more work is needed to better understand the nature of the relationship between food insecurity and ED pathology with regard to factors such as development and ED presentation.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Food insecurity has also been associated with poor health outcomes in children, including higher rates of acute infections, developmental problems, mental health problems [8], and chronic conditions [3,[9][10][11][12]. Food insecurity disproportionately affects households in rural areas, headed by a single adults with children [13], predominantly Black (non-Hispanic) households [14], and households with children under the age of six-many of the same groups that are socially vulnerable to disasters [15]. Disasters also increase risk for food insecurity as prevalence is higher among individuals who experience a change in their life circumstances such as changes in financial obligations, household composition, or housing stability [13,16], all possible consequences of disasters for exposed households.…”
Section: Introductionmentioning
confidence: 99%
“…From an ecological perspective, the health outcome of food insecurity is influenced by factors from across the socioecological model. Individual level factors such as physical and mental health have been associated with food insecurity [34]; a person's race and ethnicity, income, and partnership can also influence such issues [14,[43][44][45][46]. At the household or social level, housing stability, social support, coping, and family decision making under financial constraint influence food security [47][48][49].…”
Section: Introductionmentioning
confidence: 99%